Enhancing the Sustainability of Small and Medium Enterprises (SMEs) through Islamic FinTech: A Comprehensive Review of Emerging Trends (2018-2024) - Anggara, Muhamad Rafi; Nuraeni, Nuraeni (Civilization Research: Journal of Islamic Studies, 2025)
This research explores the role of Sharia Financial Technology (Sharia FinTech) in enhancing SME financing and sustainability, aligning with the 2030 Sustainable Development Goals (SDGs) by integrating sustainable finance principles and Environmental, Social, and Governance (ESG) aspects. Using a systematic literature review of 12 articles published between 2018 and 2023, the study analyzes the effectiveness of Sharia FinTech in overcoming financing barriers faced by SMEs in Indonesia and Malaysia. The findings highlight that Sharia FinTech fosters financial inclusion, supports sustainable entrepreneurship, and aids in achieving SDG targets, particularly in sectors like agriculture. However, challenges such as financial mismanagement and limited digital literacy remain. This research emphasizes the need for stronger financial ecosystem partnerships and the promotion of digital literacy to maximize the potential of Sharia FinTech in contributing to sustainable economic growth. The study's implications suggest that advancing Islamic FinTech could play a pivotal role in bridging financing gaps and fostering long-term SME resilience, crucial for economic and environmental sustainability in both nations.